Effect of stifle angle on the magnitude of the tibial plateau angle measurement in dogs with intact and transected cranial cruciate ligament - Aulakh, K. S.; Harper, T. A. M.; Lanz, O. I.; Daniel, G. B.; Werre, S. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
Objective: To determine the effect of stifle angle on the magnitude of the radiographic tibial plateau angle (TPA) in normal and cranial cruciate ligament (CCL) -deficient stifles.Methods: Three pairs of canine cadaver hind-limbs from three skeletally mature dogs were positioned in a custom-made positioning device. A lateral radiograph of each specimen was obtained before and after transection of the CCL at four stifle angles (90°, 110°, 135° and 140–150° [i.e. maximum extension]), based on goniometric measurements. Four observers determined the radiographic TPA twice for each radiograph with a minimum of two days between each measurement. The radiographic TPA measurements in all specimens at different stifle angles with intact CCL and transected CCL were compared with mixed-model ANOVA. The effect of stifle angle, CCL transection, and interaction between the two on observer TPA measurement variability was also determined using the coefficient of variation.Results: Tibial plateau angle was not statistically different in the stifle angles for either the intact or transected CCL. There was also no statistical difference for TPA between intact and transected CCL groups at each of the stifle angles. Stifle angle, CCL transection and interaction between the two did not have any significant effect for intra-observer and inter-observer variation.Clinical significance: The angle of the stifle during radiography does not influence the magnitude of the TPA measurement as determined on true lateral radiographs of the stifle and tibia in cadaveric canine limbs.
Keywords: Cranial cruciate ligament; tibial plateau angle; stifle angle; tibial plateau levelling osteotomy